Correlação de imagem digital e modelagem numérica aplicada à determinação de propriedades elásticas em revestimentos de argamassa sob tração - Lacerda, Benício de Morais (Universidade do Vale do Rio dos Sinos, 2023)
Cementitious coating mortar, which works adhered to ceramic or concrete substrates, is a construction material in constant evolution. The elastic properties of the mortar are influenced by the properties of the substrate, the mortar and the interfacial connection between them, where adhesion occurs, and have a great influence on the durability of the system. This work aims to systematize a methodology for applying digital image correlation (DIC) and using numerical modeling to evaluate the elastic properties of coating mortars applied to ceramic substrates when subjected to tensile stress. A single batch of mortar was used, applied to two types of ceramic substrates. The samples were subjected to accelerated carbonation in a chamber with 3% CO2 concentration for a period of 147 days and subsequently subjected to the effect of degradation through accelerated aging resulting from 20 cycles of wetting and drying. The work consisted of two stages, one experimental and the other numerical. In the experimental stage, a test program was developed in order to quantify and evaluate the parameters of tensile adhesion strength, modulus of elasticity and Poisson's ratio in tests monitored by digital image correlation. The second stage consisted of modeling and numerical simulation of the experimental program using, as input data, the average results obtained from digital image correlation. The experimental results indicated that there are differences in elastic modulus throughout the thickness of the same coating, which decrease from the external face, towards the central region and the interface with the ceramic substrate. The tensile adhesion strength among the REF samples was higher compared to the aged and carbonated samples. Numerical simulation allowed the construction and analysis in finite elements of a model suitable for the proposed scale of the experimental study based on the DIC results. The boundary conditions applied in the numerical models under the tensile bond strength test directly influenced the interface connection, a region susceptible to rupture planes, as well as its global behavior.
Keywords: Resistência de aderência à tração; Módulo de elasticidade; Coeficiente de Poisson; Carbonatação; Envelhecimento acelerado; Correlação de imagem digital; Tensile bond strength; Elasticity modulus; Poisson coefficient; Carbonation; The accelerated aging process; Digital image correlation; ACCNPQ::Engenharias::Engenharia Civil